Kierunki rozwoju wybranych miast Kotliny Kłodzkiej na podstawie ich strategii rozwoju ze szczególnym uwzględnieniem inwestycji w zakresie infrastruktury komunikacyjnej - Rogowska, Małgorzata (Directions in Development of Kłodzko Subregion Self-Governed Units and the Role of Investments in Infrastructure, 2006)
The article describes directions in development of local self-governed units of Kłodzko subregion. Neither city nor local self-governed unit or subregion can deal with competitive environment and achieve its strategic goals without having good condition of the infrastructure. The units should put some afford to create the condition to conduct the infrastructural investments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 409-419